Wokół zagadnienia "gatunkowej predestynacji leksyki" = On the issue of "genre predestination of lexis" - Uździcka, Marzanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The content of the article is an attempt to apply Professor Stanisław Borawski`s thesis on the genre predestination of lexis to use in specific linguistic behaviors which he documented in a book "Słownictwo potoczne listów Zygmunta Miłkowskiego do Juliana Łukaszewskiego [1867-1895]" (Common Vocabulary of Zygmunt Miłkowski`s Letters to Julian Lukaszewski [1867-1895]). The thesis is used in the perspective of general vocabulary`s function to formulate scientific judgments based on the analysis of six manuscript lectures by Władysław Majewski from 1848-1850.
Keywords: predestynacja leksyki; metoda statystyczna; leksyka ogólna; leksyka częsta; wykład; predestination of lexis; statistical method; general lexis; common lexis; lecture